2020
DOI: 10.3390/cells9112466
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Jun N-Terminal Kinase, a Potential Therapeutic Target in Autoimmune Arthritis

Abstract: The c-Jun-N-terminal kinase (JNK) is a critical mediator involved in various physiological processes, such as immune responses, and the pathogenesis of various diseases, including autoimmune disorders. JNK is one of the crucial downstream signaling molecules of various immune triggers, mainly proinflammatory cytokines, in autoimmune arthritic conditions, mainly including rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis. The activation of JNK is regulated in a complex manner by upstream kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…The ERK and MAPK pathways were also related to most AS targets of Danshensu. The MAPK pathway including ERK, JNK and p38 pathways, is involved in inflammatory signaling, regulation of cell proliferation and differentiation, and activation of the immune system ( Lai et al, 2020 ). The ERK1/2, JNK, and p38 pathways regulate osteoblast differentiation ( Chen et al, 2016 ), and inhibition of MAPK signaling was shown to reduce the expression levels of ALP and OCN ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ERK and MAPK pathways were also related to most AS targets of Danshensu. The MAPK pathway including ERK, JNK and p38 pathways, is involved in inflammatory signaling, regulation of cell proliferation and differentiation, and activation of the immune system ( Lai et al, 2020 ). The ERK1/2, JNK, and p38 pathways regulate osteoblast differentiation ( Chen et al, 2016 ), and inhibition of MAPK signaling was shown to reduce the expression levels of ALP and OCN ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs phosphorylate a variety of intracellular proteins, including transcription factors that consequently regulate the expression of genes involved in cell proliferation, differentiation, survival, cellular stress and inflammatory responses. MAPKs contribute to the production of the inflammatory cytokines, chemokines, prostaglandins, MMPs and growth factors involved in joint inflammation and destruction and are important players in the RA pathogenesis [42][43][44]. The therapeutic potential of MAPKs as drug targets has been clearly demonstrated using specific inhibitors in experimental models of arthritis [45][46][47].…”
Section: Ra Pathwaysmentioning
confidence: 99%
“…Although the structure and sequences of all JNKs are similar, containing well conserved features observed in other MAPKs, JNK1 and JNK3 closely resemble each other, with JNK2 containing sequence differences in the kinase domain ( Gupta et al, 1996 ). Despite the multifaceted role of JNKs in cell signaling, JNK has still been viewed as a promising target for several disease areas ( Lai et al, 2020 ; Yung and Giacca, 2020 ; Abdelrahman et al, 2021 ). Our interest comes from its role in mediating inflammatory and immunological responses ( Lai et al, 2020 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the multifaceted role of JNKs in cell signaling, JNK has still been viewed as a promising target for several disease areas ( Lai et al, 2020 ; Yung and Giacca, 2020 ; Abdelrahman et al, 2021 ). Our interest comes from its role in mediating inflammatory and immunological responses ( Lai et al, 2020 ; Chen et al, 2021 ). Indeed, JNK inhibition has been demonstrated to downregulate the production of several proinflammatory transcription factors and cytokines ( Kaminska et al, 2009 ; Lai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation